2019
DOI: 10.1111/hel.12654
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication rates with concomitant and tailored therapy based on 23S rRNA point mutation: A multicenter randomized controlled trial

Abstract: Background:We evaluated the efficacy of tailored therapy based on point mutation presence identified with the dual-priming oligonucleotide (DPO)-based multiplex polymerase chain reaction (PCR) method compared with concomitant therapy. Materials and methods:Subjects were randomly assigned concomitant therapy (amoxicillin 1 g, clarithromycin 500 mg, metronidazole 500 mg, and lansoprazole 30 mg twice/day for 14 days) or tailored therapy (amoxicillin 1 g, clarithromycin 500 mg, and lansoprazole 30 mg twice/day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 40 publications
(57 reference statements)
5
50
1
Order By: Relevance
“…Based on the Maastricht V consensus reports, the above treatment is appropriate in countries with less than 15% resistance to clarithromycin. There are numerous, important factors (human and bacterial) in reducing the effect of H. pylori treatment, of which the antibiotic resistance seems to be the most significant [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Maastricht V consensus reports, the above treatment is appropriate in countries with less than 15% resistance to clarithromycin. There are numerous, important factors (human and bacterial) in reducing the effect of H. pylori treatment, of which the antibiotic resistance seems to be the most significant [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We have just performed (in 2020) an updated meta-analysis comparing empirical versus susceptibility-guided treatment of H. pylori , 59 including 40 studies. 60100 When only assessing first-line treatments, better efficacy results were obtained, overall, with the susceptibility-guided strategy (although the results were borderline statistically significant). However, when considering only empirical up-to-date first-line quadruple regimens (that is excluding the suboptimal triple therapies) no differences in efficacy were found versus the susceptibility-guided group.…”
Section: What Is the Comparative Effectiveness Of Susceptibility-guided Versus Empirical Strategy For First-line Treatment?mentioning
confidence: 97%
“…11 However, H pylori is difficult to culture in clinical settings because it requires microaerobic and high-CO 2 culture conditions. 11 Several lines of evidence suggest that the 2143A > G mutation in H pylori 23S ribosomal RNA (rRNA) is related to clarithromycin resistance and eradication failure, [12][13][14][15] and screening for this mutation is likely to be an effective alternative method to identify clarithromycin resistance in H pylori. 12 We previously reported that the presence of 2143G in H pylori 23S rRNA is an independent risk for eradication failure, which reached approximately 60% in response to clarithromycin-based triple therapy, and patients with 2143A-2182C mutations showed a moderate risk with approximately 10% eradication failure.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several lines of evidence suggest that the 2143A > G mutation in H pylori 23S ribosomal RNA (rRNA) is related to clarithromycin resistance and eradication failure, [12][13][14][15] and screening for this mutation is likely to be an effective alternative method to identify clarithromycin resistance in H pylori. 12 We previously reported that the presence of 2143G in H pylori 23S rRNA is an independent risk for eradication failure, which reached approximately 60% in response to clarithromycin-based triple therapy, and patients with 2143A-2182C mutations showed a moderate risk with approximately 10% eradication failure. 15 However, the polymerase chain reaction (PCR)-based method to amplify DNA fragments and identify targeted mutations is also time-consuming, 16 and it is emerged the need for simple method to detect mutations.…”
Section: Introductionmentioning
confidence: 99%